Drug loading comparison of commercial ibuprofen on magnetite nanoparticles surface by UV-Vis spectrophotometry and acid-alkali titration by a factorial design of experiments - Felipe Ocampo Osorio; Esteban Noé Villanueva Badillo; Dariana Geraldine Erazo Rondón; Erika Tatiana Muñoz Arango; Abilo Andrés Velásquez Salazar; Alvaro Andrés Velasquez Torres; Oscar Moscoso Londoño; Elisabeth Restrepo Parra; César Leandro Londoño Calderón (Elsevier, 2023)
The drug efficacy for the pathologies treatments depends on several physicochemical properties of the drug. Among these, solubility is one of the most important and is directly related to the bioavailability of the drug. Ibuprofen is a popular drug used for the treatment of different diseases. However, its dissolution rate in aqueous media is limited, which causes undesirable adverse effects on the patient. One of the possibilities to solve this challenge is loading ibuprofen on the surface of the nanoparticles for drug delivery. However, some challenges related to complicated experimental procedures, expensive chemical precursors, the techniques for ibuprofen quantification, and the loading efficiency continue to be a problem. This work reports the synthesis of magnetite nanoparticles and the straightforward loading with commercial ibuprofen in a mixed ethanol/water solution without intermediate surfactants, stabilizers, or linkers. XRD, SEM, FT-IR, Magnetometry, UV-Vis Spectrophotometry, and DLS techniques allowed for determining the samples' structure, morphology, functional groups, magnetism, and agglomerate size. A complete factorial Design of Experiments allowed for comparing the encapsulation efficiency for two exposure and centrifugation times (20 and 40 min) by UV-VIS and Acid-alkali titration. The results suggest that the magnetic separation and centrifugation (< 2000 RPM) were inappropriate for nanoparticle decantation. This produces an underestimation of the ibuprofen adsorbed by the nanoparticles. Under our experimental conditions, 20 min is enough to achieve maximum encapsulation efficiency (14%) without surfactants or binders.